Estimation of roughness‐induced scattering losses in III‐nitride laser diodes with a photoelectrochemically etched current aperture (Phys. Status Solidi A 4∕2016). Issue 4 (April 2016) - Megalini, Ludovico; Shenoy, Renuka; Rose, Kenneth; Speck, James P.; Bowers, John E.; Nakamura, Shuji; Cohen, Daniel A.; DenBaars, Steven P.
Abstract : Constricting the current to flow to the center of the lasing mode by laterally and controllably etching the active region can improve the performance of optoelectronic and electronic devices by eliminating current leakage pathways and reducing the attendant dc‐rf dispersion. Differently from other III‐V semiconductors, the III‐nitrides lack conventional wet etchants and photoelectrochemical (PEC) etching has been proposed as an alternative to create selective and controllable undercut. Ludovico Megalini et al. (pp.953–957 ) have achieved CW operation of a III‐N current aperture blue laser diode (CALD) by PEC etching the active region of a (202̅1̅) InGaN multi quantum well (MQW) laser diode. Here they estimate the roughening‐induced scattering optical modal losses caused by imperfect PEC etching in such structure by using a 3D Volume Current Model in conjunction with roughness data obtained by AFM and SEM image processing of the remnant PEC‐etched waveguides after the top p‐layers were removed by focused ion beam cuts. Finally they propose possible ways to mitigate these scattering losses and therefore improve the differential efficiency of the final device.